Efficient organic light-emitting diodes by insertion a thin lithium fluoride layer with conventional structure - Kim, Y.; Park, Y.; Choi, J.; Kim, J.; Ju, B. (2006)
Insertion of a thin lithium fluoride (TLF) layer between an emitting layer (EML) and an electron transporting layer has resumed in the developement of a highly efficient and bright organic light-emitting diode (OLED). Comparing with the performance of the device as a function of position with the TLF layer in tris-(8-hydroxyquinoline) aluminum (Alq3), we propose the optimal position for the TLF layer in the stacked structure. The fabricated OLED shows a luminance efficiency of more than 20 cd/A, a power efficiency of 12 lm/W (at 20 mA/cm2), and a luminance of more than 22 000 cd/m2 (at 100 mA/cm2), respectively. We suggest that the enhanced performance of the OLED is probably attributed to the improvement of carrier balance to achieve a high level of recombination efficiency in an EML. ？ 2006 Taylor & Francis Group, LLC.